2009
DOI: 10.1038/aja.2008.60
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sexual activity status and influencing factors in men after surgery for hypospadias

Abstract: The aim of this study was to compare the long-term postoperative status of hypospadiac patients by analysing their sexual psychology, sexual behaviour, sexual function and influencing factors. A total of 130 hypospadiac patients hospitalized between January 1988 and December 2007 were followed up with questionnaires using Zung's Self-rating Depression Scale (SDS), Self-rating Anxiety Scale (SAS), a self-designed sexual function questionnaire and a 5-item version of the International Index of Erectile Function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Wang et al. demonstrated that subjects undergoing multiple operations have lower scores on anxiety and depression scales but show no difference in sexual behavior when compared to subjects undergoing a single operation [13]. These aspects, therefore, cannot be addressed by our study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Wang et al. demonstrated that subjects undergoing multiple operations have lower scores on anxiety and depression scales but show no difference in sexual behavior when compared to subjects undergoing a single operation [13]. These aspects, therefore, cannot be addressed by our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Due to a hypospadias and its subsequent correction, this process may be disturbed by a potential functional or cosmetic problem with the penis. Despite this, only a few studies report on patients’ long‐term satisfaction and sexual and psychosexual consequences [8–20]. These studies, however, have shown contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Because this study is a sub-analysis of our previous study, it has the same kind of limitation as have been already documented in the earlier report. One drawback, inevitable in this type of study, was the limited response rate to the questionnaires, although our response rate at 28.4% was comparable to that in other similar studies [6, 14]. Limited response can cause selection bias, but we would like to note that there was no significant difference in background between the responders and non-responders with respect to hypospadias severity as reported in the previous study [15] and the type of initial repair procedure as described in this report.…”
Section: Discussionsupporting
confidence: 70%
“…Questions about sexual function were based on the International Index of Erectile Function and the Brief Male Sexual Function Inventory (O'Leary et al, 1995; Rosen et al, 1997; Mykletun et al, 2006). These instruments have been used in the Chinese population in many previously reported studies (He et al, 1976; Yu et al, 2007; Guo et al, 2009; Wang et al, 2009; Xie et al, 2009).…”
Section: Methodsmentioning
confidence: 99%